2021
DOI: 10.14366/usg.20179
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based automated quantification of the hepatorenal index for evaluation of fatty liver by ultrasonography

Abstract: Purpose: The aim of this study was to develop and validate a fully-automatic quantification of the hepatorenal index (HRI) calculated by a deep convolutional neural network (DCNN) comparable to the interpretations of radiologists experienced in ultrasound (US) imaging.Methods: In this retrospective analysis, DCNN-based organ segmentation with Gaussian mixture modeling for automated quantification of the HRI was developed using abdominal US images from a previous study. For validation, 294 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The agreement between AI-HRI measured by two examiners (ICC = 0.64) was good, and it was in the range of the interobserver agreement reported for manually labeled HRI (ICC = 0.58–0.68) [ 11 ]. The correlation between the two observers’ measurements was weaker with AI-HRI than with conventional HRI (r s =0.57 vs. Pearson’s r =0.70).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The agreement between AI-HRI measured by two examiners (ICC = 0.64) was good, and it was in the range of the interobserver agreement reported for manually labeled HRI (ICC = 0.58–0.68) [ 11 ]. The correlation between the two observers’ measurements was weaker with AI-HRI than with conventional HRI (r s =0.57 vs. Pearson’s r =0.70).…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound scans were performed by an expert radiologist with more than ten years of experience in abdominal ultrasound. The AI-HRI model used in this study has been trained and validated by Cha et al on pre-transplantation liver US scans as has been reported previously [ 11 ]. For AI-HRI measurements, a right intercostal or subcostal view was obtained in supine patients and showing the longitudinal cross-section of the right kidney and the right liver lobe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 compares machine learning algorithms for liver disease diagnosis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In the current study, a high level of diagnostic performance was observed.…”
Section: Discussionmentioning
confidence: 99%
“…An HRI model based on CNNs was also tested for NAFLD evaluation. Cha et al [ 33 ] reported that an automated approach had no significant difference in hepatic measurements and HRI calculations compared with experienced radiologists, which indicated that the aid of deep learning could reduce a radiologist’s workload and improve the residents’ diagnostic accuracy. In this study, an automated HRI calculation algorithm was used, including liver and kidney segmentation, kidney ROI extraction, liver ROI extraction, and calculation of the HRI.…”
Section: Application Of Ai In Diffuse Liver Diseasementioning
confidence: 99%